The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.analchem.9b00546
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between Inactive and Active States of Rhodopsin by Atomic Force Microscopy in Native Membranes

Abstract: Membrane proteins, including G protein-coupled receptors (GPCRs), present a challenge in studying their structural properties under physiological conditions. Moreover, to better understand the activity of proteins requires examination of single molecule behaviors rather than ensemble averaged behaviors. Force-distance curve-based AFM (FD-AFM) was utilized to directly probe and localize the conformational states of a GPCR within the membrane at nanoscale resolution based on the mechanical properties of the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 79 publications
3
30
0
Order By: Relevance
“…To further demonstrate the mechanical stability of the RBD, we employed a validated structure-based modelling approach. 15,28,29,31,32 Our computational structure-based study (see Fig. 3) shows that the RBD is a mechanically stable component in the spike (see next section) and also identifies the structural motif (see Fig.…”
Section: Resultsmentioning
confidence: 94%
“…To further demonstrate the mechanical stability of the RBD, we employed a validated structure-based modelling approach. 15,28,29,31,32 Our computational structure-based study (see Fig. 3) shows that the RBD is a mechanically stable component in the spike (see next section) and also identifies the structural motif (see Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Early hypotheses regarding possible GPCR tertiary structures depicted the receptor as a simple switch which existed in either an inactive or active state. However, a growing body of evidence suggests that activation of GPCRs is not a binary operation, but rather that the tertiary structure conformation can exist in a series of intermediate states 50 , with a range of activity levels possible across the distribution of conformations as shown by fluorescence-based techniques 30,73 , FNMR 32 , AFM 74 , electron microscopy 75 , X-ray crystallographic studies 38 , and theoretical simulations using crystal structures 2,33,[76][77] . From crystal structure studies of individual GPCRs, it has been observed that the intracellular region of TM1, TM3, TM5, TM6, and TM7 move outward from one another when ligand is bound 2 , with TM6…”
Section: Discussionmentioning
confidence: 99%
“…, rhodopsin (opsin + chromophore) (Rho) is both a light receptor and a structural protein ( 4 , 96 ). Disabling the chromophore-binding site in opsin ( 97 ) results in a constitutively active visual pigment molecule ( 98 ), but also changes the structural integrity of the unliganded opsin in the disk membranes ( 99 , 100 ), thereby leading to a gain-and-loss of function (GLF). Thus, different mutations in one gene can lead to a variety of diseases such as autosomal dominant (adRP) and autosomal recessive retinitis pigmentosa (arRP) and autosomal dominant congenital stationary blindness (CSNB) ( 101 , 102 , 103 , 104 ), all of which can be caused by mutations in the opsin gene.…”
Section: Genetic Disease-causing Changes In the Visual Cyclementioning
confidence: 99%